Dampak faktor sosial ekonomi orang tua terhadap hasil belajar: systematic literature review - Ratna Wijaya; Reni Suciari Duwi Utami; Mohammad Edy Nurtamam (Universitas Sebelas Maret, 2025)
Abstract. This study aims to analyze the impact of parents' socioeconomic factors on students' learning outcomes using the Systematic Literature Review (SLR) method. The research sample consists of 20 scientific articles published between 2014 and 2024, selected through the PRISMA approach to ensure relevance. Data collection was conducted by filtering academic literature using Publish or Perish (PoP). Data validity was maintained through a rigorous selection process based on inclusion and exclusion criteria. Data analysis was performed using thematic synthesis, categorizing findings based on economic, social, and mediating factors. The results indicate that parents' socioeconomic status significantly influences students' learning outcomes, primarily through access to educational resources, learning motivation, and parental support. Mediating factors, such as the learning environment and parenting style, also shape this relationship. This study concludes that inclusive education policies, improved educational facilities, and parental involvement can help bridge the academic gap caused by economic disparities. The recommendations include strengthening scholarship programs, providing psychological support for underprivileged students, and enhancing access to educational technology to improve students' learning outcomes equitably.Kata kunci: socioeconomic status, learning outcomes, parents.